Fibrous dysplasia and Klippel–Trenaunay syndrome: a rare association. Issue 8 (4th August 2018) - Nishimoto, Soh; Moriguchi, Kurumi; Ishise, Hisako; Ikemura, Konosuke
Abstract: Fibrous dysplasia is a rare congenital disorder, with abnormal hypertrophy of affected bone. A 17-year-old girl with a protrusion on her right forehead presented and was diagnosed as craniofacial fibrous dysplasia. Although she had no gait problem, her right leg was longer than the other. She had vascular malformation on the right leg. The condition was diagnosed as Klippel–Trénaunay syndrome, which also is a rare disorder. As the prevalence of these disorders is scarce, the probability of coincidental association of them is extremely low. No previous report about the association of fibrous dysplasia and Klippel–Trénaunay syndrome could be found. We concluded that, those two rare congenital disorders arose coincidentally in this patient.